Identification of EGF-NF-κB-FOXC1 signaling axis in basal-like breast cancer - Chung, Stacey (Cell Commun Signal, 2017)
BACKGROUND: The pathogenesis of human basal-like breast cancer (BLBC) is not well understood and patients with BLBC have a poor prognosis. Expression of the epidermal growth factor receptor (EGFR) and nuclear factor-κB (NF-κB) is well-known to be upregulated in BLBC. The forkhead box C1 (FOXC1) transcription factor, an important prognostic biomarker specific for BLBC, has been shown to be induced by EGF and is critical for EGF effects in breast cancer cells. How FOXC1 is transcriptionally activated in BLBC is not clear. METHODS: Luciferase reporter assays were performed to show that NF-κB-p65 enhances FOXC1 promoter activity in BLBC cells (MDA-MB-468). Electrophoretic mobility shift assay, biotinylated oligonucleotide precipitation assay, and chromatin immunoprecipitation assay were used to show that NF-κB interacts and binds to the promoter region of FOXC1. RESULTS: In this study, we demonstrate that NF-κB is a pivotal mediator of the EGF/EGFR regulation of FOXC1 expression by binding to the FOXC1 promoter to activate FOXC1 transcription. Loss or inhibition of NF-κB diminished FOXC1 expression. CONCLUSION: Collectively, our findings reveal a novel EGFR-NF-κB-FOXC1 signaling axis that is critical for BLBC cell function, supporting the notion that intervention in the FOXC1 pathway may provide potential modalities for BLBC treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12964-017-0180-3) contains supplementary material, which is available to authorized users.